The Structure of Humor in Psycho Stand-Up Comedy by Margaret Cho - Anindita Dewangga Puri (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2020)
This research aims to analyze the structure of humor in Psycho stand-up comedy employed by Margaret Cho. It is qualitative descriptive research. The main source of this research is the oral data in Psycho stand-up comedy performed by Margaret Cho. There are three steps to find out the aim of this research: the data collection from stand-up comedy entitled Psycho, the analysis of the data, and the last is the display of the result. After all of the data is collected, the researcher tries to find out the structure of Psycho stand-up comedy by using the sequence of joke theory by Rutter and the structure theory of stand-up comedy by Scarpetta and Spagnolli. Based on the data analysis, the researcher finds that this stand-up comedy is divided into three parts: the opening, the core, and the closing. A master of ceremony conducts the opening. The body of this stand-up comedy consists of 31 bits, and in one bit, there are parts such as setup, transition, punchline, act-out, and expanding successful jokes. Margaret Cho delivers the closing of this stand-up comedy as an appreciation to her audiences. The researcher also finds that the punchline that is done repeatedly becomes the characteristics of Psycho stand-up comedy employed by Margaret Cho.